A Life Cycle Perspective on Changes in Earnings Inequality among Married Men and Women - Pencavel, John (The Review of Economics and Statistics, 2006)
The connection between changes in earnings inequality of individuals and changes in family earnings involves several links: the movements in the employment of different family members, the association between changes in husbands' and in wives' earnings, and patterns of assortative mating. A decomposition of the logarithm of the coefficient of variation in family earnings identifies these links. The data on the dispersion of family earnings are organized not simply over time, but also by age. The growth in wives' relative employment and earnings has partly offset the effects on family earnings inequality of the increase in husbands' earnings inequality.